2004
DOI: 10.1634/stemcells.22-2-216
|View full text |Cite
|
Sign up to set email alerts
|

IL‐3‐Dependent Early Erythropoiesis Is Stimulated by Autocrine Transforming Growth Factor Beta

Abstract: Autocrine/paracrine transforming growth factor beta (TGF-β β) is an important regulator of stem cell quiescence and generally suppresses stem cell proliferation. However, we show here that during the first few days of an erythroid cell culture from adult blood stem cells, the presence of neutralizing antibodies against TGF-β β had a suppressive effect on subsequent erythropoiesis, indicating a stimulatory action of autocrine TGF-β β. -CD34 + stem cells, and the latter were also much less dependent on IL-3. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…TGF-β, as well as tumor necrosis factor alpha and IFN gamma, is a powerful inhibitor of erythropoiesis both in vivo and in vitro. The suppressive effect of TGF-β on E-lineage cell proliferation is accompanied by an acceleration of terminal maturation (30)(31)(32)(33)(34).…”
Section: Suppressive Effect Of Tgf-β On Proliferation Of Eps/e-meps Imentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β, as well as tumor necrosis factor alpha and IFN gamma, is a powerful inhibitor of erythropoiesis both in vivo and in vitro. The suppressive effect of TGF-β on E-lineage cell proliferation is accompanied by an acceleration of terminal maturation (30)(31)(32)(33)(34).…”
Section: Suppressive Effect Of Tgf-β On Proliferation Of Eps/e-meps Imentioning
confidence: 99%
“…Importantly, hEPs never generated MegK cells even under serum-free culture conditions, which allow optimal growth and differentiation of MegK progenitors (48). CD105 is part of the TGF-β receptor complex (29); several studies have revealed an inhibitory effect of TGF-β on E-lineage cell proliferation, causing accelerated terminal maturation by blocking the cell cycle of immature cells (30)(31)(32)(33)(34). However, these studies targeted CD34…”
Section: Cd105mentioning
confidence: 99%
“…On average, only 77% of the erythroblasts generated in HEMA culture were viable (Table 3). The low viability of ex vivo generated erythroid cells is attributed to the range of apoptosis‐inducing agents released by the cells during culture 42,43 . A similar slight (18%), but not significant (p > 0.5), reduction in number of viable erythroid cells was observed after thawing short‐ and long‐term‐stored cells (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…The score of this match ranks 2 out of 17254 upstream regions. Tgfb1 is known to be involved in IL-3-dependent early erythropoiesis [52]. Strong matches are also seen for Klf1 (rank 42/17254), a very important transcriptional regulator of erythropoeisis, and for Gata-5 (rank 73/17254), which, like Gata-1, binds GATA DNA sites.…”
Section: Resultsmentioning
confidence: 79%